Follow-up of thyroid cancer patients using rhTSH -preliminary results - Petrich, T.; Börner, A. R.; Weckesser, E.; Soudah, B.; Otto, D.; Widjaja, A.; Hofmann, M.; Kreipe, H. H.; Knapp, W.H. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: In the follow-up of patients with advanced stage thyroid cancer radioiodine scintigraphy, F-l 8-FDG PET and tumormarker hTg using stimulation with recombinant human TSH (rhTSH) were compared to the results of same diagnostic procedures during TSH-suppression or endogenous TSH-stimulation. Methods: 30 patients were investigated in hypothyroidism and after application of rhTSH regarding the serum hormone concentrations, hTg, radioiodine scans and FGD-PET scans. Results: Radioiodine avidity and FDG uptake were significantly higher in 7/30 and 3/5 patients, respectively, compared to endogenous stimulation or TSH-suppression. In about one third of patients hTg increased more than 30%. Conclusion: Our preliminary results indicate a sufficient feasibility and sensitivity of rhTSH not only in the follow-up by hTg and radioiodine scan but also in FDG-PET.
Keywords: Thyroid cancer; recombinant TSH; PET; FDG; radioiodine; thyroglobulin